Aplicação da Lei de Lenz-Faraday em experimentos potencialmente significativos para o ensino aprendizagem - Fares, Mohamad Imad Escobar (2017)
Master's Dissertation submitted to the Post-Graduation Program Federal University of Mato Grosso in the Professional Master's Degree Course in Physics Teaching (MNPEF), as part of the requirements to obtain a Master's Degree in Physics Teaching The proposal of this work is an alternative for the improvement of the learning process of Physics of High School, through experiments potentially significant for the teaching of Physics especially for electromagnetism. The teaching of non-high school physics in the traditional way may be difficult to understand theoretically for a few moments required of students a capacity for abstraction a little higher than the costume. It was chosen as a group of samples of the students of two classes of the third year of high school of the school Maria Macedo Rodrigues, located in the municipality of Várzea Grande MT. Aiming at a greater practical theoretical involvement, a sequence of two potentially significant experiments, related to electromagnetic induction, associated with support materials, was constructed as well as a study of the construction of each experiment. At the end of the experiments, a questionnaire related to the subject was applied. A methodology used incorporated data collection, participatory observations, lectures and a multiple-choice questionnaire. An educational product offering consisting of an electric generator with low cost materials associated with an electric motor that is currently in compliance with the present as instructions for its manufacture to be mandatory for other people who are interested in the subject. The results obtained are very interesting and productive from the pedagogical point of view, since all the students are lenient, they claimed an improvement in the understanding of the phenomena addressed.